Authentic Leadership and Followership International Perspectives (Palgrave Studies in Leadership and Followership,, 2018)
This book shines a spotlight on two missing foci of authentic leadership research: international and follower perspectives. The concept of 'authenticity' has been in vogue since the times of Greek philosophy, but it wasn't until the 1990s that leadership scholars seriously began to study the topic of authentic leadership. This new collection brings together empirical research and theoretical contributions to provide insights into the follower perspectives of authentic leadership around the world. Covering topics such as leader self-awareness, gender, psychological capital, embodied leadership and followership, and unethical conduct, the book features a Foreword written by William L. Gardner, one of the original scholars on authentic leadership. .